Jean-Michel Kalmbach: Suomi-ranska opiskelusanakirja (’Finsk-fransk studieordbok’); Seppo Sundelin: Ranska-suomi opiskelusanakirja (’Fransk-finsk studieordbok’) - Mattila, Heikki E.S. (LexicoNordica, 1995)
the dictionaries concerned, sources used by the authors, reference system between articles, appendices, phraseology, vocabulary of different styles (vulgar, colloquial, Iiterary) and jargons, proper names, and bibliography. The reliability of the translations given in the dictionaries is only exarninated with respect to the legal terminology included in them. The general opinion of the reviewer is very positive. He, however, makes some propositions for later editions. For example, more proper names could be added and, besides, readers could be told how foreign proper names have normally been adapted to the systems of the languages concerned (orthographic alterations etc.). Since no dictionary can be perfect, more detailed bibliographies would also be very useful.